Reduced switch count dual-output T-type multilevel converter - Ahmed S. Hussein (2022)
A new dual-outut multilevel converter topology based on neutral point connection is introduced. The topology significantly reduces the switch count, especially with increasing output voltage levels. Hence, it is referred to as the Reduced Switch Count Dual-output T-type (RSC-DT) multilevel converter. A level detection PD-PWM modulation technique was implemented to drive the converter's output and maintain the dc-link capacitor voltage balancing. The neutral point voltage balancing was achieved by utilizing the redundant states occurring under three-phase operation. The simulation results shows an effective control algorithm and normal operation of the converter. A study on the dc-link capacitor balancing limitation has also been carried out.